The electronic structure of VO in its ground and electronically excited states: a combined matrix isolation and quantum chemical (MRCI) study - Hübner, Olaf; Hornung, Julius; Himmel, Hans-Jörg (The journal of chemical physics, 2015)
The electronic ground and excited states of the vanadium monoxide (VO) molecule were studied in detail. Electronic absorption spectra for the molecule isolated in Ne matrices complement the previous gas-phase spectra. A thorough quantum chemical (multi-reference configuration interaction) study essentially confirms the assignment and characterization of the electronic excitations observed for VO in the gas-phase and in Ne matrices and allows the clarification of open issues. It provides a complete overview over the electronically excited states up to about 3 eV of this archetypical compound.